1997
DOI: 10.1074/jbc.272.33.20313
|View full text |Cite
|
Sign up to set email alerts
|

Protein Oxidation in Aging, Disease, and Oxidative Stress

Abstract: The demonstration that oxidatively modified forms of proteins accumulate during aging, oxidative stress, and in some pathological conditions has focused attention on physiological and nonphysiological mechanisms for the generation of reactive oxygen species (ROS) 1 and on the modification of biological molecules by various kinds of ROS. Basic principles that govern the oxidation of proteins by ROS were established in the pioneering studies of Swallow (1), Garrison (2, 3), and Scheussler and Schilling (4) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
2,064
2
32

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 3,007 publications
(2,164 citation statements)
references
References 43 publications
37
2,064
2
32
Order By: Relevance
“…It is established that an elevated level of protein oxidation is associated with aging (Berlett andStadtman, 1997, Smith, et al, 1992). For example, mitochondrial aconitase (Yan, et al, 1997, Yarian, et al, 2006 and adenine nucleotide translocase can lose their functional activities due to age-related oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that an elevated level of protein oxidation is associated with aging (Berlett andStadtman, 1997, Smith, et al, 1992). For example, mitochondrial aconitase (Yan, et al, 1997, Yarian, et al, 2006 and adenine nucleotide translocase can lose their functional activities due to age-related oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The sulphur containing amino acids such as methionine and cysteine are more susceptible to oxidation by ROS and are converted to disulphides and methionine sulphoxide [89,90] respectively. However in biological systems, only these two oxidized forms of proteins can be converted back to their native form by two different enzymes namely disulfide reductases and methionine sulfoxide reductases respectively [91][92][93][94]. The ROS mediated attack of different amino acids results in the formation of different oxidation products such as, tryptophan forms nitrotryptophan, kynurenine, formylkynurinine; Phenylalanine forms 2,3-Dihydroxyphenylalanine, 2-, 3-, and 4-hydroxyphenylalanine; Tyrosine forms 3,4-Dihydroxyphenylalanine, tyrosine-tyrosine cross-linkages, Tyr-O-Tyr, cross-linked nitrotyrosine; Histidine forms 2-Oxohistidine, asparagine, aspartic acid; Arginine forms glutamic semialdehyde; Lysine forms a-Aminoadipic semialdehyde; Proline forms 2-Pyrrolidone, 4-and 5-hydroxyproline pyroglutamic acid, glutamic semialdehyde; threonine forms 2-Amino-3-ketobutyric acid; leucine and valine residues form hydroxyl residues [91].…”
Section: Proteinsmentioning
confidence: 99%
“…Perhaps more interesting is that when the frequencies of Cys, Met, and His are added to the frequencies of the above-mentioned aromatic residues, the r value of the correlation with the position of the sequences along the third axis is higher (r ‫ס‬ 0.71). These six residues have in common the property of being the preferential targets of reactive oxygen species and can act as sinks for radical fluxes through electron transfer between amino acids on the protein (Dean et al 1993;Berlett and Stadtman 1997). It has been suggested that these residues could confer some resistance to reactive oxygen species in the anaerobic unicellular eukaryote G. lamblia (Garat and Musto 2000).…”
Section: Amino Acid Frequenciesmentioning
confidence: 99%